SOCIAL REPRESENTATIONS ABOUT HEALTH EDUCATION AMONG COMMUNITY HEALTHCARE ASSISTANTS: COURSES OF ACTION FOR PERMANENT EDUCATION - Christiano Adson Barbosa Lima; Antonio Luís Parlandin dos Santos; Arlete Marinho Gonçalves; Elizabeth Teixeira; Horácio Pires Medeiros (Universidade Federal do Paraná, 2012)
This qualitative study had as its aim to analyse the structure of social representations of health education among community healthcare assistants in the city of Oriximiná in the state of Pará. The Theory of Social Representations was adopted as a framework, in a structural perspective. Data were collected via Vergés' free association with the phrase health education among 61 community healthcare assistants, processed by the EVOC2003 software and analyzed by a Vergés four-quadrant chart. The results point to a positive representational structure, with the terms prevention and orientation appearing as central representational elements, and raise questions for guiding processes of permanent education. It is concluded that the representations are related to a complex web involving community healthcare assistants' actions.